2018
DOI: 10.1007/s00467-018-4049-5
|View full text |Cite
|
Sign up to set email alerts
|

Urine biomarkers of chronic kidney damage and renal functional decline in childhood-onset systemic lupus erythematosus

Abstract: • Levels of osteopontin and adiponectin measured at the time of kidney biopsy are good predictors of histological damage with lupus nephritis. • Only about 20% of children with substantial kidney damage from lupus nephritis will have an abnormally low urine creatinine clearance. • Continuously high levels of biomarkers reflecting lupus nephritis activity are risk factors of declining renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
0
31
2
Order By: Relevance
“…Many of these proteins have already been reported as potential biomarkers for renal dysfunction, mostly in native kidney diseases. α 1 -B glycoprotein, 14 afamin 15 , apolipoprotein A1 and A4, 16 , 17 , 18 , 19 , 20 leucine-rich α 2 -glycoprotein 1, 21 , 22 , 23 α 1 -antitrypsin, 24 , 25 antithrombin, 26 , 27 transferrin, 28 , 29 and Ig heavy chain α 1 and γ 4 are not specific for disease processes or histologic lesions and have been associated with a wide range of kidney diseases or kidney dysfunction. It could be that some of the proteins in the panel might represent general injury or injury mechanisms, rather than being specific for antibody-mediated injury.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these proteins have already been reported as potential biomarkers for renal dysfunction, mostly in native kidney diseases. α 1 -B glycoprotein, 14 afamin 15 , apolipoprotein A1 and A4, 16 , 17 , 18 , 19 , 20 leucine-rich α 2 -glycoprotein 1, 21 , 22 , 23 α 1 -antitrypsin, 24 , 25 antithrombin, 26 , 27 transferrin, 28 , 29 and Ig heavy chain α 1 and γ 4 are not specific for disease processes or histologic lesions and have been associated with a wide range of kidney diseases or kidney dysfunction. It could be that some of the proteins in the panel might represent general injury or injury mechanisms, rather than being specific for antibody-mediated injury.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a non-invasive method to detect and monitor kidney injury would be a major advance over the current need for a kidney biopsy. Numerous studies have attempted to study urine to understand renal pathology in lupus, generally with a focus on urine proteins, and have identified factors associated with lupus nephritis, including TWEAK and MCP1 [105][106][107][108][109] . Immune cells accumulate in urine of patients with lupus nephritis 51,[110][111][112] , raising the possibility that these cells reflect renal pathology.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Whether changes in urinary transferrin filtration and excretion represent an epiphenomenon or an accomplice to renal injury in lupus nephritis remains a tantalizing question. A prospective study reported continued high urinary transferrin levels in pediatric SLE patients who displayed renal function decline within 12 months of biopsy (33). The same group reported that marked reduction of urinary transferrin during treatment is predictive of achieving remission (34).…”
Section: Discussionmentioning
confidence: 98%